The risk of bilirubin encephalopathy in neonatal hyperbilirubinemia - Oktay, Remzi; Satar, Mehmet; Atıcı, Aytuğ (The Turkish Journal of Pediatrics, 1996)
Jaundice is the most common and one of the most annoying problems that can occur in the newborn. Although most jaundiced infants recover without any serious problem, there is always a risk of bilirubin encephalopathy during the period of hyperbilirubinemia. The relationship between encephalopathy and serum free bilirubin levels was investigated in 83 newborn infants (40 premature, 43 mature) with unconjugated hyperbilirubinemia. A complete physical examination was done in all patients, and signs of bilirubin encephalopathy were noted if present. The serum free bilirubin level exceeded 0.1 mg/dl in 13 infants, and 12 of them showed signs of encephalopathy. On the other hand, none of the infants whose serum free bilirubin levels were below 0.1 mg/dl showed signs of encephalopathy. Although there is a significant positive correlation between serum total and free bilirubin levels, it is not clear at what total bilirubin level free bilirubin will appear. Serial determinations of free bilirubin appear to be more helpful in the management of hyperbilirubinemia in infants with an increased risk of bilirubin toxicity.